Популяризація діяльності Науково-методичної підкомісії МОН України в соціальній мережі Facebook - Мина, Жанна; Яворська, Наталія (Видавництво Львівської політехніки, 2017)
This article analyzes the activities of scientific and methodogical subcommission ministry of Education of Ukraine and its popularization on Facebook with the rapid development of information and communication technologies and gradual globalization of information space. Stresses the importance of public dialogue, publication and discussion of important information.
Keywords: соціальні мережі; Науково-методична підкомісія; Facebook; освіта; студенти